Real-time physiological monitoring for management of normobaric hypoxic training toward wearable system implementation - Hisatsune, K.; Yamakawa, T. (Journal of Digital Life, 2022)
As a method to prevent lifestyle diseases, normobaric hypoxic training has been attracting attention. However, its exercise load and safety in non-athletes remain unclear. In this study, 20 healthy university students underwent a 15-min exercise test in a normobaric hypoxic room set at two different oxygen concentrations (O2: 20% and 16%), and the exercise load and safety were evaluated. The test comprised walking within the upper and lower limits of the heart rate (HR) calculated via the Karvonen method. The results showed that in case of 16% O2, the same energy was consumed despite significantly lower walking speed and distance than those in case of 20% O2. Therefore, it is suggested that the Karvonen method is effective in setting the load for hypoxic training. In addition, real-time monitoring of arterial oxygen saturation (SpO2) could be used to evaluate the safety of hypoxic training. Based on these results, we have developed a wearable pulse oximeter that can measure both HR and SpO2 from the earlobe and a dedicated smartphone application for analysis. If these can be practically applied, hypoxic training can be conducted safely that will contribute to the prevention of lifestyle diseases and the consequent extension of healthy life expectancy.